Microtubules as a versatile reference standard for expansion microscopy - Rajdeep Chowdhury; Tiago Mimoso; Abed Alrahman Chouaib; Nikolaos Mougios; Donatus Krah; Felipe Opazo; Sarah Köster; Silvio O. Rizzoli; Ali H. Shaib (Communications Biology)
Abstract Expansion microscopy (ExM) is continually improving, and new ExM variants need to be validated on well-defined biological structures. There is no consensus on validation structures for ExM, especially as nuclear pore complexes or DNA nanorulers are not popular for ExM studies. Here we propose that microtubules should be used for ExM validation. The diameter of microtubules immunostained using primary and secondary antibodies is sufficiently large for the validation of techniques with resolutions better than 50 nm. For techniques with higher precision (up to ~10 nm), microtubules can be assembled and imaged in vitro, using a protocol that we introduce here. Alternatively, a cellular extraction procedure can be employed, followed by labeling the peptide chains of the tubulin molecules with NHS-ester fluorophores. Finally, for nanometer-scale techniques, single tubulin molecules can be analyzed. We conclude that microtubules are valuable structures for the validation of ExM and related technologies.